Features of Cytokine Storm Identified by Distinguishing Clinical Manifestations in COVID-19 - Shen, Wei-Xi; Luo, Rong-Cheng; Wang, Jing-Quan; Chen, Zhe-Sheng (Frontiers in Public Health, 2021)
Coronavirus disease 2019 (COVID-19) is caused by a new coronavirus, namely severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is currently spreading all over the world. In this paper, we developed a practical model for identifying the features of cytokine storm, which is common in acute infectious diseases and harmful manifestation of COVID-19, by distinguishing major and minor clinical events. This model is particularly suitable for identifying febrile and infectious diseases like COVID-19. Based on this model, features of cytokine storm and pathogenesis of COVID-19 have been proposed to be a consequence of the disequilibrated cytokine network resulting from increased biological activity of transforming growth factor-β (TGF-β), which induces certain clinical manifestations such as fatigue, fever, dry cough, pneumonia, abatement and losing of olfactory, and taste senses in some patients. Research and clarification of the pathogenesis of COVID-19 will contribute to precision treatment. Various anti-TGF-β therapies may be explored as potential COVID-19 treatment. This novel model will be helpful in reducing the widespread mortality of COVID-19.